Development of an islamic values-based early childhood education curriculum to foster children's religious character - Robingatin; Anwar, Syaiful (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: The development of an Islamic values-based early childhood education (ECE) curriculum is a fundamental necessity for fostering children's religious character during early childhood, a developmental stage commonly referred to as the golden age. Objective: This study aims to describe the development of an Islamic values-based Early Childhood Education (ECE) curriculum in fostering children's religious character. Methods: This study employed a qualitative research design using a library research approach. Data were collected from relevant reference sources, including books and scholarly journal articles. The data were analyzed using content analysis to identify, interpret, and synthesize concepts related to the development of an Islamic values-based ECE curriculum. Results: The findings indicate that the development of an Islamic values-based ECE curriculum should be systematically designed and implemented by establishing the Qur'an and the Sunnah as its primary foundations, which are integrated into the dimensions of faith (iman), worship (ibadah), and moral conduct (akhlaq). The study also reveals that children's religious character can be effectively fostered through teaching strategies and learning methods that are aligned with the developmental stages and potentials of young children, including role modeling, habituation, training, advice, disciplinary measures, discipline enforcement, persuasion, and the consistent application of educational rules. Conclusion: Furthermore, the implementation of an Islamic values-based curriculum has a significant positive impact on nurturing religious attitudes, cultivating habitual worship practices, and developing noble moral behavior from an early age.